How do Stem Cell Transplantation Outcomes Differ between Various Types of Leukemia (Acute Lymphoblastic vs Acute Myeloid Leukemia) : A Systematic Review - Luthfiyya Syafiqa Tahany; I Putu Hartawan Mataram (International Medical Journal Corp. Ltd, 2025)
Introduction : This systematic review investigates the differential outcomes of stem cell transplantation (SCT) in various types of leukemia, specifically acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL). SCT is a crucial therapeutic approach for these aggressive hematologic malignancies, offering potential for long-term remission. Understanding the varying outcomes between AML and ALL is vital for optimizing treatment strategies, including conditioning regimens, donor selection, and post-transplant care. Methods : The study adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligibility criteria included studies focusing on adult patients ( ≥ 18 years) diagnosed with ALL or AML, examining allogeneic or autologous SCT, comparing outcomes between ALL and AML, reporting clinical outcomes like overall survival (OS), disease-free survival (DFS), treatment-related mortality (TRM), graft-versus-host disease (GVHD) incidence, or relapse rates, including ≥ 10 patients, and involving human subjects. Data extraction focused on study design, participant characteristics, SCT details, primary outcomes, and study limitations. A comprehensive search strategy utilizing Boolean MeSH keywords was applied to databases such as PubMed, Semantic Scholar, Springer, and Google Scholar. Results : From 15 included studies showed that overall survival rates varied significantly, with some reports indicating 3-year OS of 35% for AML versus 0% for ALL, while others showed 5-year OS of 23.5% for AML versus 70% for ALL. Engraftment rates generally exceeded 89%. Relapse rates ranged widely from 4% to 49%. Acute GVHD incidence varied from 19.8% to 69%. Conditioning regimens significantly impacted outcomes; high-dose cytarabine improved survival in AML, whereas etoposide increased mortality risk in ALL. Novel T-cell manipulation techniques and mesenchymal stem cell use showed promise in reducing severe acute GVHD. In conclusion : SCT outcomes differ considerably between AML and ALL due to variations in disease biology, conditioning regimens, GVHD prophylaxis, and stem cell sources. Tailoring transplantation protocols to the specific leukemia subtype and individual patient characteristics is crucial for improving survival and minimizing complications. Continued research into novel conditioning approaches, immune modulation, and cell source optimization is essential to advance SCT as a curative therapy for acute leukemias. Keywords: Stem Cell Transplantation, Acute Myeloid Leukemia, Acute Lymphoblastic Leukemia, Overall Survival, Graft-versus-Host Disease, Relapse Rate.